KEPEMIMPINAN TRANSFORMASIONAL DAN PERILAKU KERJA INOVATIF: MODERASI BERBAGI PENGETAHUAN - Ni Kadek Cantika Dewi; Made Zola'Sela Bolabali; I Nengah Aristana (Universitas Triatma Mulya, 2023)
Small and medium industries have an essential role in the economic growth of a country. However, this industry is currently facing various challenges due to changes in an increasingly competitive environment. The purpose of this research is to analyze and explain the influence of transformational leadership on innovative work behavior, and to determine the role of knowledge sharing in the relationship between transformational leadership and innovative work behavior. The population of this study was all export-oriented small and medium industries, totaling 42. Then the sample was determined using the Krejcie and Morgan formulation so that the total sample was 38 industries. Research respondents were selected by recruiting five employees from each industry so the number of respondents who contributed was 190 people. The research findings show that transformational leadership and knowledge sharing positively and significantly affect innovative work behavior. However, knowledge sharing does not moderate the influence shown by transformational leadership on innovative work behavior. Key Word: Transformation leadership, innovative work behavior dan small medium industry